"Yes, you can": Conversational assessment in the classroom and its role in the management of institutional and social goals. (September 2019) - Lynett, Adrienne
Abstract: Human sociality depends on people's ability to relate to and understand one another. Language and other communicative resources are frequently deployed in interaction in order to acquire, maintain, understand and apply this information about one another. This article investigates the role of assessment as a resource for the expression of empathy and thus the maintenance of social affiliation and intersubjectivity in a literacy classroom for indigenous immigrants in the United States. Assessment is a standard pedagogical device, used commonly by teachers to evaluate student performance; they are also frequent in ordinary conversations, in which they can and often do build empathic affiliation. Both kinds of assessments occur in the literacy classroom, with one type often giving way to the other. This study thus demonstrates this dynamic aspect of assessment sequences and their potential to reveal group affiliation in certain cases. The article first discusses assessments deployed by the instructor, typical classroom sequences that offer a venue for public evaluation of student activity. Analysis then turns to examples of assessments made by students, which can invite second assessments that result in a multi-party interaction that, in turn, builds group affiliation. After analysis of these sequences, implications for learning are discussed.